Moderation of the relationship between Toxoplasma gondii seropositivity and trait impulsivity in younger men by the phenylalanine-tyrosine ratio. (December 2018) - Peng, Xiaoqing; Brenner, Lisa A.; Mathai, Ashwin J.; Cook, Thomas B.; Fuchs, Dietmar; Postolache, Nadine; Groer, Maureen W.; Pandey, Janardan P.; Mohyuddin, Farooq; Giegling, Ina; Wadhawan, Abhishek; Hartmann, Annette M.; et al.
Highlights: Toxoplasma gondii ( T. gondii) was previously associated with higher impulsivity. Dopaminergic system regulates impulsivity, and T. gondii secretes dopamine (DA). DA precursors (phenylalanine [Phe]; tyrosine [Tyr]) change with mild inflammation. We measured and related T. gondii, Phe, Tyr and impulsivity in healthy subjects. Only young men with both high Phe:Tyr and T. gondii (+) reported high impulsivity. Abstract: Previously, we reported that Toxoplasma gondii ( T. gondii) -seropositivity is associated with higher impulsive sensation seeking in younger men. As dopaminergic and serotonergic signaling regulate impulsivity, and as T. gondii directly and indirectly affects dopaminergic signaling and induces activation of the kynurenine pathway leading to the diversion of tryptophan from serotonin production, we investigated if dopamine and serotonin precursors or the tryptophan metabolite kynurenine interact with the T. gondii –impulsivity association. In 950 psychiatrically healthy participants, trait impulsivity scores were related to T. gondii IgG seropositivity. Interactions were also identified between categorized levels of phenylalanine (Phe), tyrosine (Tyr), Phe:Tyr ratio, kynurenine (Kyn), tryptophan (Trp) and Kyn:Trp ratio, and age and gender. Only younger T. gondii -positive men with a high Phe:Tyr ratio, were found to have significantly higher impulsivity scores. There were no significant associations in other demographic groups, including women and older men. No significant effects or interactions were identified for Phe, Tyr, Kyn, Trp, or Kyn:Trp ratio. Phe:Tyr ratio, therefore, may play a moderating role in the association between T. gondii seropositivity and impulsivity in younger men. These results could potentially lead to individualized approaches to reduce impulsivity, based on combined demographic, biochemical and serological factors.